Determining correlations for solar chimneys in buildings with wind interference: A numerical approach. (December 2021) - Zamora, B.
Highlights: Performance study of solar thermal chimney under buoyancy and wind driven forces.Numerical procedure with low-Re turbulence modeling, including ABL correct simulation. The presence of a cover produces a non-negligible worsening of performance. Practical correlations are presented including the impacts of relevant parameters. Relevant differences in performance for opposite directions of wind are encountered. Abstract: The impact of wind on the performance of a solar thermal chimney is analyzed by numerical investigation. The chosen geometry for the dwelling-solar chimney system can be considered as sufficiently generic and representative, and similar to the buildings assisted with passive systems that are currently being designed. Both the wind driving and the buoyancy forces are included in the study. The developed numerical approach takes into account the atmospheric boundary layer for specifying the acting wind, and includes a low-Reynolds treatment of turbulence at walls for obtaining a detailed description of the airflow. The procedure is validated enough, and permit us to address a systematic analysis of the influence of temperature difference (10–100 K, corresponding to Rayleigh numbers from 3.616 × 10 9 to 3.616 × 10 10 and wind speed ranging 0–10 m/s) on the behavior of chimney in ventilation mode. Two opposite directions of the wind are studied, finding clear different impacts on the solar chimney performance. For the more favorable wind direction, a complete set of correlations for the induced mass-flow rate and the dimensionless heat transfer coefficient is proposed, aimed at practical engineering applications.